The Role of Social Support in the Face of Vulnerability to Economic Strain: Perspective from Sarawak Urban Area - Yew Kang, Liew; Shirly Siew Ling, Wong; Rosita, Hamdan; Dayang Affizzah, Awang Marikan (Science Publishing Corporation Inc, 2025)
This research investigates the complex interactions between economic strain, social support, resilience, and well-being in Sarawak in the aftermath of the economic disruptions brought about by the COVID-19 pandemic. Based on a sample of 290 participants, the study utilized structural equation modeling to address three primary objectives: examining the relationships between economic strain, social support, well-being, and resilience; assessing the mediating role of social support in the relationship between economic strain and well-being; and evaluating its mediation effect between economic strain and resilience. The initial findings corroborate the presence of significant associations between economic strain and the three constructs of well-being, resilience, and social support. Social support has been identified as a crucial mediator that modulates the interaction between economic strain and well-being and between economic strain and resilience. This abstract succinctly summarizes the central inquiry of the study, focusing on how economic adversities in the post-pandemic period influenced individual and community well-being in Sarawak, with an emphasis on the mitigating role of social support networks.